Citizen science breathes new life into participatory agricultural research. A review - Gevel, Jeske M.J, van de; Etten, Jacob van; Deterding, Sebastian (Springer, 2020)
Participatory research can improve the efficiency, effectiveness, and scope of research processes, and foster social inclusion, empowerment, and sustainability. Yet despite four decades of agricultural research institutions exploring and developing methods for participatory research, it has never become mainstream in the agricultural technology development cycle. Citizen science promises an innovative approach to participation in research, using the unique facilities of new digital technologies, but its potential in agricultural research participation has not been systematically probed. To this end, we conducted a critical literature review. We found that citizen science opens up four opportunities for creatively reshaping research: (i) new possibilities for interdisciplinary collaboration, (ii) rethinking configurations of socio-computational systems, (iii) research on democratization of science more broadly, and (iv) new accountabilities. Citizen science also brings a fresh perspective on the barriers to institutionalizing participation in the agricultural sciences. Specifically, we show how citizen science can reconfigure cost-motivation-accountability combinations using digital tools, open up a larger conceptual space of experimentation, and stimulate new collaborations. With appropriate and persistent institutional support and investment, citizen science can therefore have a lasting impact on how agricultural science engages with farming communities and wider society, and more fully realize the promises of participation.